Análise eletrocardiográfica, da pressão arterial e de citocinas séricas em cães epilépticos - Trevisan, Yolanda Paim Arruda (2024)
Idiopathic epilepsy is the most common chronic neurological disease in dogs, with a prevalence of 0.75%, and is associated with reduced life expectancy, neurobehavioral changes and a greater risk of developing comorbidities in the interictal period. In humans with epilepsy there is a greater chance of sudden death (Sudden Unexpected Death in Epilepsy - SUDEP), however the mechanism is not yet clear, but high blood pressure can lower the convulsive threshold and precipitate epileptic seizures. At the same time, the onset of crises is related to an increase in sympathetic tone, which can increase blood pressure, affect the rhythm and frequency of heartbeats, as well as electrocardiographic changes. Animal studies show that neuroinflammatory pathways contribute to the development and progression of epilepsy and can be targeted for therapy. In general, neuroinflammation is a normal response that helps maintain homeostasis, however, a prolonged or very intense neuroinflammatory response can become unfavorable, leading to cellular dysfunction. Based on this, the importance of the occurrence of idiopathic epilepsy with hypertension or changes in heart rhythm in veterinary medicine is highlighted, as well as the inflammatory profile in canine epilepsy. The objectives of this study were: 1) to evaluate blood pressure values and electrocardiographic findings, in addition to hematological, serum and urinary biochemical and blood gas parameters in dogs with idiopathic epilepsy treated with phenobarbital 2) to investigate the inflammatory profile of cytokines in dogs with epilepsy idiopathic and structural under treatment compared to non-epileptic dogs. The values of the complete QRS and ST interval were statistically different between the groups of epileptic dogs and healthy dogs, however blood pressure did not show a statistical difference. Regarding cytokines, the serum concentration of IFN-γ was significantly different between the control group and dogs with structural epilepsy. With these results, although it is not a longitudinal study, idiopathic epilepsy suggests that it is a disease that can promote changes in cardiac conduction and epileptic dogs showed reduced serum values of pro-inflammatory cytokines. Based on the results, suggested that epilepsy interferes with electrical conduction due to the autonomic activities triggered during the epileptic seizure and that dogs should undergo cardiological monitoring due to secondary complications. Likewise, the search for peripheral biomarkers, such as cytokines, can help to develop new treatments that act on the inflammatory pathways of epilepsy.